THE INFLUENCE OF TEACHER’S TEACHING STYLE AND LEARNING DISCIPLINE ON STUDENTS’ COGNITIVE ABILITY AT SMP NEGERI 3 MOTOLING TIMUR - Dolonseda, Herman; Dame, Joubert M.; Lendongan, Agsel (Literacy: Jurnal Pendidikan Ekonomi, 2023)
This study aims to determine the effect of the teacher’s teaching style and learning discipline on the cognitive abilities of students at SMP Negeri 3 Motoling Timur. This test strategy is a learning technique with an example of 75 individuals. The procedure used in collecting information is a survey strategy (poll) and documentation. The results of the examination were dissected using various recurrence direct examinations, basic connection examinations and various connection examinations. The results showed: (1) There is an influence between the Teacher’s Teaching Style on the Cognitive Ability of students of SMP Negeri 3 Motoling Timur by 44.89% with t count > t table = 7.71 > 2.04 and F count > F table. Keywords: Teacher’s Teaching Style, Learning Discipline, Students’ Cognitive Ability